Mission to Paris - Alan Furst (Phoenix, 2013)
Frederic Stahl, born of Viennese intelligentsia, ran away to sea at 17. Arriving in America, his matinee idol looks took him to Hollywood and a life of movies and women. After war breaks out in Europe, he goes to Paris to shoot a film. He is soon drawn into a clandestine world of foreign correspondents, exiled Spanish republicans, & spies.